2013
DOI: 10.2478/aep-2013-0022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Suitability of Amaranthus Caudatus L. and Ricinus Communis L. in Phytoextraction of Cadmium and Lead from Contaminated Substrates

Abstract: Abstract:The phytoextraction is a process that uses living plants for cleaning up the heavy metals from contaminated soil. The cadmium and lead contamination of soils results from the application of sludge or urban composts, fertilizers, pesticides, motorization, metallurgy, and different technological processes. In industrial terrain the content of cadmium and lead in soils has increased in the recent years. This study was undertaken to evaluate the potential of Amaranthus caudatus L. 'Atropurpureus' and Rici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Castor bean (R. communis, Euphorbiaceae) is a fast-growing, perennial shrub, with a well-developed root system, tolerance to poor soil fertility, high economic and biomass value. These traits make castor bean a candidate species for phytoremediation (16)(17)(18)(19).…”
Section: Lead Toxicity Bioassaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Castor bean (R. communis, Euphorbiaceae) is a fast-growing, perennial shrub, with a well-developed root system, tolerance to poor soil fertility, high economic and biomass value. These traits make castor bean a candidate species for phytoremediation (16)(17)(18)(19).…”
Section: Lead Toxicity Bioassaysmentioning
confidence: 99%
“…Castor bean has the potential to tolerate and accumulate heavy metals like Cd (13,14 ), As (67,88), Ni (68,89,99), Zn (100), and Cu (70,77) and high tolerance to Cd, Cu and Zn (90). R. communis is a good candidate for the removal of DDTs (dichloro diphenyl trichloroethane) and Cd from contaminated soils (78).…”
Section: Castor Is a Wizard Of Phytoremediationmentioning
confidence: 99%
“…Sainger et al investigated the element uptake by plants growing in highly contaminated soils and reported a high adaptatability of some plant species growing in such environment. For example, Bosiacki et al (2013) observed increasing yield of Ricinus communis aboveground biomass with increasing Cd content in cultivation substrate. Clearly, plants growing at the highly contaminated sites developed a range of mechanisms that may be ivolved in the detoxifi cation of risk elements such as reduced uptake of these elements, their binding to the cell wall, immobilization, exclusion of the plasma membrane, reduction of heavy metal transport, compartmentalisation and metal chelation by tonoplast located transporters, expression of stress proteins, role of organic acids and aminoacids, etc.…”
Section: Introductionmentioning
confidence: 98%
“…Amaranthus species attract a special interest in the context of Zn stress due to their importance as a source for valuable nutrient-rich foods and fodder crops (Achigan-Dako et al, 2014) with pronounced stress tolerance and well-characterized potential for HM phytoremediation (Watanabe et al, 2009;Bosiacki et al, 2013;Ko et al, 2014). From the point of primary metabolism, this genus is featured with C4 type of photosynthesis (Ludwig, 2016) and elevated production of oxalic acid (Gélinas and Seguin, 2007;Osmolovskaya et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%